Blueprinting construction logistics services for quality improvement. Issue 1 (2nd January 2023) - Gremyr, Ida; Bäckstrand, Jenny; Fredriksson, Anna; Gatenholm, Gabriella; Halldórsson, Árni
Abstract: Construction logistics services can, if implemented with high quality, positively impact both efficiency and sustainability of construction projects. However, present quality management frameworks have not been developed for temporary multi-actor contexts, such as construction, which is largely lacking industrialised processes. Still, construction logistics service providers provide service offerings to temporary settings and could thus benefit from a service quality perspective. Applying this perspective, this study supports the quality improvement of construction logistics services by using a service modularity approach to identify the services to prioritise for improvement. Building on interviews, concept mapping, and a service blueprint of a construction logistics setup, a priority matrix for improvements is developed. The first step in using this matrix is to operationalise the construction logistics setup in modules based on blueprinting. Second, the matrix evaluates the modules against nine empirically derived improvement enablers such as practices and forums for learning, and data measurements enabling the comparison and follow-up of construction logistics services. In conclusion, the priority matrix helps focus the improvements on modules with high likelihood of successful improvements. Improvements that can become sustained over time through the reuse of standardised modules in upcoming projects.